PENGUASAAN KOMPETENSI GURU KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI BERPRESTASI DALAM MENINGKATKAN KINERJA GURU SD DENGAN SISTEM FULL DAY SCHOOL DI KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to determine how far the influence of:Â  Mastery Teacher competence, leadership and achievement motivation Principal jointly and severally on the performance of elementary school teachers with a system full day in Wonosobo regency.This research was conducted in three primary schools with full day School system in Wonosobo regency. This research is a quantitative study using a survey method. The subjects of this study were teachers from SD IT InsanMulia, SD Al Madina, SD Muhammadiyah Bilingual Full Day School (MBF) Al Adzkiya ,totaling 55 respondents. This study used a test used because of time constraints. Collecting data in this study using a questionnaire or a questionnaire. Data analysis techniques in this study using multiple regression with three predictors. Hypothesis Testing is jointly carried out using F-test.The results showed that (1) mastery of teacher competence, leadership and achievement motivation Principal jointly affect the performance of teachers with a contribution of 79.4% (2) mastery of teacher competence independently affect the performance of the teachers with the effective contribution of 25, 24%, (3) the leadership of Principal independently affect the performance of the teachers with the effective contribution of 14.36%, (4) achievement motivation of teachers independently affect the performance of the teachers with the effective contribution of 39.81%. This suggests that the three independent variables are mastering competence of teachers, school leadership and achievement motivation considerable influence on the performance of teachers. If the three independent variables together, or individually to increase, the performance of teachers will also increase.